2015
DOI: 10.1002/bjs.9783
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of patients with colorectal cancer and simultaneous liver and lung metastases

Abstract: Patients who had resection of liver and lung metastases had similar overall survival to those who had undergone removal of isolated liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 39 publications
4
81
1
1
Order By: Relevance
“…Patients with many types of cancer are at high risk of liver metastases. Moreover, tumors originating from intra‐abdominal organs, such as those of the stomach, pancreas, colon, gallbladder, bile duct, and ovary, often exhibit both peritoneal dissemination and liver metastasis . Together with the findings of our previous study , the results obtained in this study suggest that the i.p.…”
Section: Discussionsupporting
confidence: 85%
“…Patients with many types of cancer are at high risk of liver metastases. Moreover, tumors originating from intra‐abdominal organs, such as those of the stomach, pancreas, colon, gallbladder, bile duct, and ovary, often exhibit both peritoneal dissemination and liver metastasis . Together with the findings of our previous study , the results obtained in this study suggest that the i.p.…”
Section: Discussionsupporting
confidence: 85%
“…De Haas et al reported a 5‐year OS for patients with liver metastases of 58% in the time period from 2000 to 2010. Similarly, data from the LiverMetSurvey registry showed a 5‐year OS rate for patients with liver metastases of 49.6% for the period from 2008 to 2012 . For the same time interval, patients who were treated for simultaneous lung metastases and were able to achieve an R0 resection at both sites exhibited a 5‐year OS of 41%.…”
Section: Discussionmentioning
confidence: 87%
“…However, it is unclear how overall survival is affected in patients who had resection of liver and lung metastases compared to those undergoing removal of isolated lung or liver metastases. 3, 18 We also did not have access to data granular enough to describe the exact location of primary tumors, and this has previously been shown to have an effect on rates and patterns of distant metastases and subsequent survival. 19, 20 However, we have no reason to suspect that the location of a primary tumor would be different based on insurance status, so this should not have substantially affected our result.…”
Section: Discussionmentioning
confidence: 99%